Preoperative visual function characteristics having an effect on the success of exotropia surgery - I. M. Boichuk; Alui Tarak (Ukrainian Society of Ophthalmologists, 2023)
Background: There are individual reports on the effect of some preoperative characteristics of visual functions (like convergence, angle of deviation, presence of fusion and type of binocular vision) on the success of exotropia surgery. To date, however, it has not been established what are the major diagnosis-related prognostic factors for the success of surgery for exotropia. Purpose: To identify the preoperative characteristics of visual functions which have an effect on the success of surgery for exotropia. Material and Methods: Of the 59 exotropes (age range, 10 to 21 years) included in this study, 33 had basic constant exotropia (group 1) and 26, intermittent exotropia (group 2). Patients underwent an ophthalmological and ortoptic examination of the motor and sensory systems of the eye. Patients with surgery success (postoperative orthotropes) were compared to those who had a residual exotropia of more than 10 prism diopters (PD) postoperatively in terms of the preoperative accommodative convergence-accommodation (AC/A) ratio, near point of convergence (NPC), distance stereopsis and near stereoacuity threshold. Results: Our analysis of the preoperative NPC, AC/A ratio and stereopsis for the group with postoperative orthotropic alignment and the group with postoperative exotropic alignment found preoperative close to normal values of AC/A ratio (4.0 ± 1.65 PD/D), NPC (8.03 ± 3.02 cm), the presence of distance stereopsis and near stereopsis (passing the 200 second of arc image on the Lang II stereo card) and the absence of medial rectus hypofunction of hyperfunction in 83.05% of patients of the former group. Conclusion: Preoperative close to normal values of AC/A ratio (4.0 ± 1.65 PD/D), NPC (8.03 ± 3.02 cm), the presence of distance stereopsis and near stereopsis (passing the 200 second of arc image on the Lang II stereo card) and the absence of medial rectus hypofunction of hyperfunction can be the factors favoring the success of exotropia surgery.